Characterization of the soybean KRP gene family reveals a key role for GmKRP2a in root development - Guo, Binhui; Chen, Lin; Dong, Lu; Yang, Chunhong; Zhang, Jianhua; Geng, Xiaoyan; Zhou, Lijuan; Song, Li (Frontiers in Plant Science, 2023)
Kip-related proteins (KRPs), as inhibitory proteins of cyclin-dependent kinases, are involved in the growth and development of plants by regulating the activity of the CYC-CDK complex to control cell cycle progression. The KRP gene family has been identified in several plants, and several KRP proteins from Arabidopsis thaliana have been functionally characterized. However, there is little research on KRP genes in soybean, which is an economically important crop. In this study, we identified nine GmKRP genes in the Glycine max genome using HMM modeling and BLASTP searches. Protein subcellular localization and conserved motif analysis showed soybean KRP proteins located in the nucleus, and the C-terminal protein sequence was highly conserved. By investigating the expression patterns in various tissues, we found that all GmKRPs exhibited transcript abundance, while several showed tissue-specific expression patterns. By analyzing the promoter region, we found that light, low temperature, an anaerobic environment, and hormones-related cis-elements were abundant. In addition, we performed a co-expression analysis of the GmKRP gene family, followed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) set enrichment analysis. The co-expressing genes were mainly involved in RNA synthesis and modification and energy metabolism. Furthermore, the GmKRP2a gene, a member of the soybean KRP family, was cloned for further functional analysis. GmKRP2a is located in the nucleus and participates in root development by regulating cell cycle progression. RNA-seq results indicated that GmKRP2a is involved in cell cycle regulation through ribosome regulation, cell expansion, hormone response, stress response, and plant pathogen response pathways. To our knowledge, this is the first study to identify and characterize the KRP gene family in soybean.